The effectiveness of four methods for stain removal from direct resin-based composite restorative materials - Hend Nahedh Al-Nahedh; Wedad Yassin Awliya (Saudi Dental Journal)
Background/purpose: Few studies investigated the best method for removing stains from different types of resin-based composite restorations and compared them to the more recently introduced nanocomposites. This study compared the effect of four methods for stain removal from composite resins; finishing with Sof-lex disks, using pumice and brush, bleaching with 10% carbamide peroxide and 38% hydrogen peroxide. Materials and methods: Twenty disk specimens were prepared. Specimens were immersed in a staining solution for 3 weeks. The stained surfaces of five specimens from each RBC material were treated with one of the treatment procedures. Colorimetric measurements were taken using spectrophotometer prior to and after staining, and then repeated after surface treatments. Color difference values were calculated. Results: One-way ANOVA indicated significant differences in color change of the three composite resin materials following staining. Filtek Z250 showed the least susceptibility to discoloration followed by Renamel, Filtek Supreme was the material most prone to discoloration. Two-way ANOVA and Tukey’s Post Hoc showed that all stain removing procedures except polishing with pumice, were able to return Filtek Z250 to clinically acceptable color difference. While bleaching with 38% carbamide peroxide was not effective with Renamel. Only pumice and 10% carbamide peroxide were able to return Renamel to clinically acceptable color difference. Conclusion: Compositions of resin-based composite resins play an important role in their susceptibility to stain and their amenability to stain removal procedures. Home bleaching showed good results for the three materials, while office bleach was the least effective. Keywords: Composites, Staining, Bleaching, Polishing, Restoration